SOSIALISASI DAN PENDAMPINGAN SERTIFIKASI HALAL PROGRAM SELF DECLARE PADA USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) BINAAN BMT MANDIRI UKHUWAH PERSADA DI KOTA MALANG - Salama, Sri Cahyaning Umi; Hakim, Rahmad (Lembaga Pengkajian dan Pengembangan Masyarakat, Yayasan Cahaya Mulia Mandiri, 2023)
Purpose of the study: The aim of this activity is to provide literacy regarding halal certification which can be done by self-declaration to MSMEs in Malang City. Methodology: There are five stages in this service, namely the preliminary stage to identify the main problems; observation stage to deepen devotion; analysis stage to determine service steps; implementation and execution level; and data evaluation and analysis level. Main Findings: Service participants follow the process according to the specified method. The service runs smoothly with several MSMEs fostered by partners who are committed to being willing to take care of their halal certification. Applications of this study: This service is useful for Malang City MSMEs who do not yet know the halal self-declaration certification process Novelty/Originality of this study: Increasing halal certification literacy among MSMEs in Malang City